HUBUNGAN PENGETAHUAN MASYARAKAT DENGAN TINDAKAN PEMELIHARAAN GIGI TIRUAN SEBAGIAN LEPASAN DI DESA COT BAROH KABUPATEN BIREUEN - Cut Ratna Keumala; Sisca Mardelita (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2021)
The use of removable partial dentures that are not accompanied by good oral hygiene results in the accumulation of plaque. Plaque formed on the surface of removable partial dentures has a negative impact on dental and oral health. Initial examination of 10 people who use removable partial dentures 7 out of 10 people do not carry out daily maintenance of dentures, 3 people always clean their removable partial dentures. This study aims to determine the relationship between public knowledge and the maintenance of removable partial dentures. This research is analytic with cross sectional design. Conducted in Cot Baroh Village, Bireuen Regency, the population of people who use removable partial dentures, the sample in this study amounted to 30 people. How to collect data through interviews. The results showed that there was a relationship between public knowledge and the maintenance of removable partial dentures in CotBaroh Village, Bireuen Regency in 2021. The results of the Chi-square test value of p value = 0.001 (< 0.05) because p < so Ha is accepted, knowledge with action 10 people (100%) good maintenance and 16 people (80.0%) poor knowledge. The results of the study concluded that there was a relationship between public knowledge and the maintenance of removable partial dentures. It is hoped that people who use removable partial dentures will increase their knowledge of how to maintain removable partial dentures by seeking information through printed or electronic media.